2014
DOI: 10.1002/hbm.22479
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative dorsal language network mapping by using single‐pulse electrical stimulation

Abstract: Abstract:The preservation of language function during brain surgery still poses a challenge. No intraoperative methods have been established to monitor the language network reliably. We aimed to establish intraoperative language network monitoring by means of cortico-cortical evoked potentials (CCEPs). Subjects were six patients with tumors located close to the arcuate fasciculus (AF) in the language-dominant left hemisphere. Under general anesthesia, the anterior perisylvian language area (AL) was first defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
129
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 47 publications
8
129
0
1
Order By: Relevance
“…Despite, some technical differences with these studies, we observed a similar waveform. The measured latencies of the first negative peak were around 20 ms in accordance with those measured in Matsumoto's group both for CCEPs and ACEPs [4,5]. In contrast, Mandonnet et al [6] measured shorter latencies for ACEPs (~ 10 ms).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Despite, some technical differences with these studies, we observed a similar waveform. The measured latencies of the first negative peak were around 20 ms in accordance with those measured in Matsumoto's group both for CCEPs and ACEPs [4,5]. In contrast, Mandonnet et al [6] measured shorter latencies for ACEPs (~ 10 ms).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the presence of axono-cortical evoked potentials (ACEPs) has been highlighted during the propagation of 1 Hz DES between white matter pathways and connected cortical sites [5,6]. Despite, some technical differences with these studies, we observed a similar waveform.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations